Ontogenetic diet shifts of a Neotropical catfish, Pimelodus maculatus (Siluriformes, Pimelodidae): An ecomorphological approach - Lima-Junior, S. E.; Goitein, R. (Kluwer Academic Publ, 2003)
This study analyses the ontogenetic diet shifts of a Neotropical catfish, Pimelodus maculatus ( Siluriformes, Pimelodidae), from an ecomorphological standpoint. We collected 241 individuals in the Piracicaba River ( Brazil) and, in the laboratory, seven morphometric variables were recorded from each specimen: standard length (SL), body depth, head length, snout length, eye diameter, mouth height and mouth width. After standardizing these measurements ( as a proportion of SL), linear regressions were run to determine whether their growth was isometric or allometric in relation to SL. The diet analysis shows that the main food item for fish in the smaller size classes is aquatic insects, while the largest individuals feed mainly on other fish. As the great majority of the morphometric variables analyzed showed isometric growth as a function of SL - which means that these fish do not change their shape significantly during their lives - the ontogenetic diet shifts may be seen as a consequence of the absolute size increment of their mouth gape, which allows individuals to maximize their energetic gain by ingesting larger prey with a higher caloric content.
Keywords: Brazil; ecomorphology; feeding; functional ecology; Piracicaba River